Ethnobotanical study of traditional knowledge, sustainable uses and management of indigenous non-medicinal plants among the Marakwet Community (Embobut Basin), Elgeyo Marakwet County (Kenya) - Wanjohi, Bernard Kariuki; Njenga, Elizabeth W; Sudoi, Vincent; Kipkore, Wilson K; Moore, Henrietta L; Davies, Mathews IJ (Ethnobotany Research and Applications, 2020)
Background: Sustainable utilization and conservation of indigenous plants requires information on the Indigenous Ecological Knowledge (IEK). This study assessed IEK on plant species identification, use and management of indigenous non-medicinal plants among the Marakwet Community in Embobut Basin in Kenya, which has a wealth of such knowledge. Methods: Plant inventories for this study were done through interviews with seven elders from the Marakwet Community who are considered to have immense IEK. The same knowledge was also evaluated among 116 local community members using checklist-based questionnaires. Results: There were 48 indigenous plant species inventoried by elders, where 4 plants (8.3%) had up to 3 indigenous names for the same plant while nine plant species (18.75%) had two names for the same plant among elders. The number of plant species that had a single and consensus name among the elders were 66.67%%. The average identification index of the species among the local was only 47.7%. Up to 58.3% of the local community members identified at least over 50% of the plant species, while 41.7% were able to identify below 50%. Conclusions: This study demonstrates loss of IEK in the Marakwets Community of Kenya. The results of the study could be used to develop culture specific sustainable utilization and conservation strategies to preserve indigenous plants of cultural value to the rural communities. This may form the first strategy in co-management of plant resources for sustainable ethnobotanical and environmental management. Key words: Traditional Ecological Knowledge, Indigenous plants, Kenya, Plant utilization